2010
DOI: 10.1074/jbc.m110.138560
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Cytokines, the Role of Astakines as Hematopoietic Growth Factors

Abstract: Hematopoiesis is the process by which hemocytes mature and subsequently enter the circulation. Vertebrate prokineticins (PKs) are known to take part in this process, as are the invertebrate prokineticin domain proteins, astakines. In Pacifastacus leniusculus, astakine 1 is essential for the release of new hemocytes into the open circulatory system of these animals. In addition to astakine 1, we have now cloned a homologue of astakine 1 with an insert of 13 amino acids, named as astakine 2. Both crustacean asta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 26 publications
4
81
0
Order By: Relevance
“…Only a few proteins specific for different hemocyte types have been identified. However, some of the proteins detected in P. leniusculus have been used to identify different differentiation pathways, showing the importance of such "marker" proteins for understanding how hematopoiesis is regulated (Lin et al, 2010;Lin and Söderhäll, 2011b;Wu et al, 2008).…”
Section: Molecular Markersmentioning
confidence: 99%
“…Only a few proteins specific for different hemocyte types have been identified. However, some of the proteins detected in P. leniusculus have been used to identify different differentiation pathways, showing the importance of such "marker" proteins for understanding how hematopoiesis is regulated (Lin et al, 2010;Lin and Söderhäll, 2011b;Wu et al, 2008).…”
Section: Molecular Markersmentioning
confidence: 99%
“…Astakines are homologues of vertebrate prokineticins, a family of small secreted cytokines of approximately 80 amino acids, which were initially isolated from the venom of the black mamba, Dendroaspis polylepis, as a nontoxic peptide [68]. Recently, it was found that Astakines play essential roles in the hematopoiesis of invertebrates [68,69].…”
Section: Novel Types Of Venom Peptides With Five Disulfide Bridgesmentioning
confidence: 99%
“…Recently, it was found that Astakines play essential roles in the hematopoiesis of invertebrates [68,69].…”
Section: Novel Types Of Venom Peptides With Five Disulfide Bridgesmentioning
confidence: 99%
“…A new astakine, astakine 2, was recently found in crayfish, and the two astakines were found to play different roles in the he-matopoiesis in crayfish (12). Astakine 1 can stimulate proliferation of Hpt cells and differentiation of Hpt cells along the SGC lineage both in vivo and in vitro, whereas astakine 2 plays an important role in the maturation of GCs in vivo.…”
mentioning
confidence: 99%